Site-specific translocation and evidence of postnatal origin of the t(1;19) E2A-PBX1 fusion in childhood acute lymphoblastic leukemia - Wiemels, Joseph L. (National Academy of Sciences, 2002)
The t(1;19) translocation yields a fusion between E2A and PBX1 genes and occurs in 5% of acute lymphoblastic leukemia in children and adults. We used chromosomal translocations and Ig heavy chain (IGH)/T cell antigen receptor (TCR) rearrangements to develop an understanding of the etiology and natural history of this subtype of leukemia. We sequenced the genomic fusion between E2A and PBX1 in 22 preB acute lymphoblastic leukemias and two cell lines. The prenatal origin of the leukemia was assessed in 15 pediatric patients by screening for the clonotypic E2A-PBX1 translocation in neonatal blood spots, or Guthrie cards, obtained from the children at the time of birth. Two patients were determined to be weakly positive for the fusion at the time of birth, in contrast to previously studied childhood leukemia fusions, t(12;21), t(8;21), and t(4;11), which were predominantly prenatal. The presence of extensive N-nucleotides at the point of fusion in the E2A-PBX1 translocation as well as specific characteristics of the IGH/TCR rearrangements provided additional evidence for a postnatal, preB cell origin. Intriguingly, 16 of 24 breakpoints on the 3.2-kb E2A intron 14 were located within 5 bp, providing evidence for a site-specific recombination mechanism. Breakpoints on the 232-kb PBX1 intron 1 were more dispersed but highly clustered proximal to exon 2. In sum, the translocation breakpoints displayed evidence of unique temporal, ontological, and mechanistic formation than the previously analyzed pediatric leukemia translocation breakpoints and emphasize the need to differentiate cytogenetic and molecular subgroups for studies of leukemia causality.